The Effect of Foreign Investment, Employment Rates, and Total Population on Educated Unemployment in Indonesia - Tri Wulandari, Anggi; Sishadiyati (International Journal of Economics (IJEC), 2023)
Unemployment has significant economic and social impacts, especially educated unemployment. The increase in the number of educated unemployed is a major problem. As of February 2022, BPS RI data indicates 8.4 million people or 5.83% of the workforce are unemployed. Educated unemployment, such as High School, Diploma, and Bachelor graduates, has the potential to support economic growth which is unfortunate if it is not handled properly. As of February 2022, according to data from the Indonesian Central Bureau of Statistics, the total number of educated unemployed in Indonesia has reached 62.4% of the total number of unemployed in Indonesia. The projection of the demographic bonus in Indonesia, Cipta Kerja Law which has the aim of overcoming employment problems by supporting foreign investment and creating jobs through ease of licensing and the fluaction of employment rates which are influenced by economic growth is the background of this research. This study analyzes the effect of foreign investment (FDI), employment rates, and total population on educated unemployment in Indonesia. The method used is the quantitative method and multiple linear regression analysis using SPSS 25. The results show that the employment rates and population have significant effect on educated unemployment while foreign investment (FDI) does not have significant effect in this study. Encouraging the quality of foreign investment remains an important role. The government should prioritize policies that support investment in potential sectors to create jobs for educated graduates. Managing population growth is also important in order to prevent increases in educated unemployment.